Outcomes of non‐cystic fibrosis‐related bronchiectasis post‐lung transplantation. Issue 6 (31st May 2022) - Kennedy, Jessica L.; Walker, Anne; Ellender, Claire M.; Steinfort, Kate; Martin, Catherine; Smith, Catherine; Snell, Gregory; Whitford, Helen
Abstract: Background: Lung transplantation is a recognised treatment for end‐stage lung disease due to bronchiectasis. Non‐cystic fibrosis (CF) bronchiectasis and CF are often combined into one cohort; however, outcomes for non‐CF bronchiectasis patients vary between centres, and in comparison with those for CF. Aims: To compare lung transplantation mortality and morbidity of bronchiectasis (non‐CF) patients with those with CF and other indications. Methods: Retrospective analysis of patients undergoing lung transplantation between 1 January 2008 and 31 December 2013. Time to and cause of lung allograft loss was censored on 1 April 2018. A case‐note review was conducted on a subgroup of 78 patients, to analyse hospital admissions as a marker of morbidity. Results: A total of 341 patients underwent lung transplantation; 22 (6%) had bronchiectasis compared with 69 (20%) with CF. The 5‐year survival for the bronchiectasis group was 32%, compared with CF (69%), obstructive lung disease (OLD) (64%), pulmonary hypertension (62%) and ILD (55%) ( P = 0.008). Lung allograft loss due to chronic lung allograft dysfunction with predominant infection was significantly higher in the bronchiectasis group at 2 years. The rate of acute admissions was 2.24 higher in the bronchiectasis group when compared with OLD ( P = 0.01). Patients with bronchiectasis spent 45.81 days in hospital per person year after transplantation compared with 18.21 days for CF. Conclusions: Bronchiectasis patients in the present study had a lower 5‐year survival and poorer outcomes in comparison with other indications including CF. Bronchiectasis should be considered a separate entity to CF in survival analysis.